Long-term dynamics of wage differentiation in the national industry in the framework of social policy - D. V. Didenko (RUDN journal of Sociology, 2025)
The article considers the interplay of factors that determined the wage ratio dynamics of two social-professional groups (blueand white-collar workers) in Russia/USSR, focusing on the core sector of material production in the industrial society and based on the official statistical data on wages. To explain the trends of total income, social expenditures and transfers, the author refers to the relevant scientific research, suggesting a new perspective for the analysis of historical data - what factors contributed to the secular cyclical dynamics of inequality and what role the income redistribution played. The factors include the patterns of supply and demand for qualifications and skills and motivations, social mechanisms and institutions. The theory of human capital, which focuses on the interaction between education and labor relations, helps to understand the role of the first group of factors. The institutional approach to the study of inequality associates its indicators with the perception and emphasizes its inherent historicity. The comparison with alternative estimates of the income inequality shows that the dynamics of the relative white-collars’ wage differential in the national industry reflects the secular cyclical trend of overall income inequality. The author argues that the egalitarian ideology of the Soviet elite affected the scale of the relative wage differential but not the direction of its trend as determined primarily by the relationship between supply and demand. Under the dominant administrative methods of balancing them in the USSR and severe wage compression in the 1960s-1980s, the enterprise management used flexible incentive instruments to stimulate productive labor, including social transfers that seem to be an inequality enhancing factor despite their declared purpose of equalizing the incomes of socially vulnerable groups. For the contemporary social policy, an important history lesson is the priority of selective and targeted use of fiscal instruments and social transfers over wage regulation.